SOCIAL ENTREPRENEURSHIP EDUCATION IN HIGHER EDUCATION - Jadmiko, Purbo; Wati, Linda; Azliyanti, Elfitra; Hadrus, Azizah Juwita (Jurnal Apresiasi Ekonomi, 2023)
Social entrepreneurship is considered a new phenomenon as a field of research, and is seen as an answer to social problems that occur. Mission and creating social value is the key goal of social entrepreneurship. However, there is still limited research that focuses on raising the issue of ways/methods to increase interest in social entrepreneurship among students (social experiential learning). The urgency of this research can be seen in the results that will be produced, namely the creation of a development model/method of fostering interest in social entrepreneurship among students through short course. The results of this study where respondents will be given a short course with prepared material (pre-test vs. pre-test) show that there is a difference in the average proportion before and after training from the 5 dimensions of Social Entrepreneur Competency (SEC), namelypersonal competence, leadership, social innovation, social values and entrepreneurial management. Even though the small workshop concept is still on a small scale, the output of this technique can be an alternative way of fostering interest in social entrepreneurship among students. Universities can improve and evaluate the design of entrepreneurship education by involving more social learning. This process can foster deeper knowledge so that they are expected to have high social awareness by manifesting an interest in becoming social entrepreneurs.